2008
DOI: 10.3171/jns/2008/108/6/1178
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in patients with cerebral hyperperfusion and cognitive impairment after carotid endarterectomy

Abstract: Although cerebral hyperperfusion syndrome after CEA sometimes results in reversible brain edema visible on MR imaging, postoperative cerebral hyperperfusion -- even when asymptomatic -- often results in impaired cognitive function without structural brain damage on MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 26 publications
3
23
0
1
Order By: Relevance
“…5,7 However, MRI, including diffusion-and T2-weighted imaging, does not always demonstrate structural brain damage associated with postoperative cognitive impairment. 8 The distribution of central benzodiazepine receptors in the human brain has been widely studied with single-photon emission CT (SPECT) using 123 I-iomazenil (IMZ). 9 -12 Benzodiazepine receptor binding potential on 123 I-IMZ SPECT images correlates with brain neural density, and a reduction in cortical benzodiazepine receptor binding indicates cortical neural damage or loss.…”
mentioning
confidence: 99%
“…5,7 However, MRI, including diffusion-and T2-weighted imaging, does not always demonstrate structural brain damage associated with postoperative cognitive impairment. 8 The distribution of central benzodiazepine receptors in the human brain has been widely studied with single-photon emission CT (SPECT) using 123 I-iomazenil (IMZ). 9 -12 Benzodiazepine receptor binding potential on 123 I-IMZ SPECT images correlates with brain neural density, and a reduction in cortical benzodiazepine receptor binding indicates cortical neural damage or loss.…”
mentioning
confidence: 99%
“…Although perioperative cerebral blood flow was not measured, and cerebral hyperperfusion syndrome was not diagnosed in the present study, the results showed that the duration of ICA cross-clamping and extent of the carotid stenosis were significantly higher in patients with postoperative cognitive impairment than in those without. Development of cerebral hyperperfusion after CeA is associated with preoperative hemodynamic impairment (11), and the longer duration of ICA cross-clamping was independent predictor of postoperative hyperperfusion (17). It indicated the postoperative cognitive impairment in the patients who had more severe carotid artery stenosis and longer duration of ICA cross-clamping might also be related to postoperative hyperperfusion.…”
Section: █ Acknowledgmentmentioning
confidence: 88%
“…Hirooka et al (11) reported all the patients with cerebral hyperperfusion syndrome developed postoperative cognitive impairment. Although perioperative cerebral blood flow was not measured, and cerebral hyperperfusion syndrome was not diagnosed in the present study, the results showed that the duration of ICA cross-clamping and extent of the carotid stenosis were significantly higher in patients with postoperative cognitive impairment than in those without.…”
Section: █ Acknowledgmentmentioning
confidence: 99%
“…According to Hirooka et al (2008), cerebral hyperperfusion after CEA is defined as a 100% increase in CBF in PWI by MRI.…”
Section: Carotid Stenting Without Postdilatationmentioning
confidence: 99%